2022
DOI: 10.1017/ash.2021.216
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic stewardship for nurses: Using e-learning modules to bridge the education gap

Abstract: Objective: The Centers for Disease Control and Prevention has called for an interdisciplinary approach to antibiotic stewardship implementation that includes front-line nurses. The literature to date has identified key factors preventing uptake by nurses: lack of education, poor communication among providers, and unit culture. Three e-learning modules were developed to address the nurses’ education regarding the roles nurses play in antibiotic stewardship, antibiotic resistance, allergy assessment, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Innovative training models are essential to cater to the practical needs of nurses [39]. Continuing education can be delivered through various formats, including faceto-face sessions, online sessions, blended learning, workshops, and seminars [18,35,40,41]. Among these options, online education stands out due to its numerous advantages like increased accessibility, fexibility, cost-efectiveness, and selfpaced learning, which overcome barriers associated with traditional face-to-face education [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Innovative training models are essential to cater to the practical needs of nurses [39]. Continuing education can be delivered through various formats, including faceto-face sessions, online sessions, blended learning, workshops, and seminars [18,35,40,41]. Among these options, online education stands out due to its numerous advantages like increased accessibility, fexibility, cost-efectiveness, and selfpaced learning, which overcome barriers associated with traditional face-to-face education [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Gullen et al 14 found that while ambulatory cancer center staff largely knew the term "antimicrobial stewardship," there were opportunities to improve knowledge about appropriate antibiotic use, particularly among nurses and other clinic staff. Catanzaro et al 15 highlighted the importance of involving nurses in antimicrobial stewardship using educational modules. Similarly, Manning et al 16 demonstrated how patient simulations can improve nursing-student awareness of their role in antimicrobial stewardship.…”
Section: Think Beyond the Hospital Walls And Beyond The Prescribermentioning
confidence: 99%
“…We compared results of the surveys taken on initial launch of the modules 3 to those taken by new hires over the next two years and did not expect there to be any significant differences.…”
Section: Introductionmentioning
confidence: 99%